Ruptured Endometriotic Cyst Mimicking Acute Appendicitis During Pregnancy - Ali Özgür Ersoy; İrem Eda Gökdemir; Ebru Ersoy; Aykan Yücel (Medical Network, 2016)
A 21-year-old primigravid pregnant woman of 33 gestational weeks applied to our Perinatology Clinic with acute abdominal pain. The pain was spreading from the midline to the right lower quadrant of the abdomen. Guarding and rebound tenderness existed in the right lower quadrant. An ultrasonographic examination revealed a single alive fetus and normal amniotic fluid. A whole blood count revealed leukocytosis and there were no signs of preterm labor or placental abruption. Fetal heart rate decelerations in a non-stress test were observed, and a decision for cesarean section and abdominal exploration were made. A healthy male baby of 2,500 grams was delivered. In the abdominal exploration, all peritoneal surfaces were coated with a dark red- to brown-colored dense material, like mud. There were two endometriotic cysts in the left ovary; one had a 6-cm mean diameter and was ruptured, while the other was intact and had a mean diameter of 2-3 cm. Both cysts were excised and sent for pathologic examination. The patient had no postoperative problems over two days and was discharged. The final pathologic diagnosis was endometriotic cysts.